Model Experiential Learning dalam Pembelajaran untuk Meningkatkan Keaktifan Bertanya Mahasiswa - Barida, Muya (Jurnal Fokus Konseling, 2018)
The activity of student asked is very important in teaching and learning. The purpose of this study was to determine the effectiveness of the model of experiential learning in teaching to enhance the activity of the student asked. Research using an experimental design with an intact group comparison models. The subjects were students of guidance and counseling that selected by purposive sampling technique. Research results through analysis techniques non-parametric Wilcoxon test values obtained with a probability of 0.028 (Î± <0.05), suggesting that the experiential learning model effective to enhance the activity of the student asked.Â Keywords:Â  experiential learning, students, activity of the student asked.